Penerapan Strategi Integrated Marketing Communication Adhiwangsa Hotel and Convention Solo pada Event So Kiss Me 2024 - Traberaldi Rafa Otniel; Rahmat Wisudawanto; Esfandani Peni Indreswari (Asosiasi Peneliti dan Pengajar Ilmu Sosial Indonesia, 2025)
In addition to personal selling, Adhiwangsa Hotel and Convention Solo also utilized other IMC tools such as direct marketing, public relations, and digital marketing to maximize the effectiveness of their promotional efforts for the